United Nations’ Provisions for Pacific Settlement of International Disputes: Array - Ola, Temitope Peter (Acta Universitatis Danubius. Relationes Internationales, 2021)
As the world’s only universal membership and general purpose international organization, it is natural for the United Nations to receive critical attention. The attention is partly because the UN is the only organization, world over, which is composed of 193 sovereign member states, influenced by numerous nongovernmental organizations, lobbied by multinational corporations, and serviced by an international secretariat. Of the many purposes and objectives identified for the UN in Chapter VI of the Charter the pursuit of pacific settlement of dispute is put forward as one main method by which the Organisation would achieve its objective of maintain global peace and security. Consequently, advancing on extant literature, this piece explores the sustenance of global peace through the provisions of Article 33 to 38 of the Charter of the UN in relation to contemporary global security challenges. This is with a view to determining whether the Chapter VI of UN Charter will continue to find relevance in the coming decades.